Reactive transport simulation of organic and inorganic carbon cycling following carbon dioxide sorption onto soil amendments in drylands - Helmrich, Stefanie; Ringsby, Alexandra J.; Maher, Kate (Frontiers in Climate, 2025)
Terrestrial nature-based climate solutions (NbCS) for carbon dioxide removal (CDR) are critical for mitigating climate change. However, the arid climates characteristic of drylands (aridity index <0.65) often limit the effectiveness of many NbCS. At the same time, drylands cover approximately 45% of the global land area and are threatened by soil degradation, necessitating the deployment of CDR methods for drylands that also promote soil health. Soil amendments with high CO2 sorption capacity, such as biochar, could provide CDR potential and soil health benefits in drylands provided they do not negatively impact the large inorganic carbon pools typical of dryland soils. The dynamics of soil CO2 are therefore critical for assessing the response of dryland systems to sorbing amendments. To assess the soil response to CO2 sorption, we developed a 1D reactive transport model of unsaturated soils in equilibrium with dissolved inorganic carbon and calcite under varying soil respiration rates and soil amendment application conditions. The simulations highlight how alteration of soil CO2 due to sorption by biochar affects dissolved inorganic carbon, pH, Ca2+, and calcite. The transient conditions that emerge, including delayed emissions of respired CO2, also emphasize the need to consider response times in monitoring campaigns based on CO2 measurements. In scenarios where soil respiration is low, as is typical in drylands, sorption becomes increasingly important. Although the CDR potential of CO2 sorption is variable and was modest relative to the overall CDR for a biochar deployment, the impacts of altered gas dynamics on soil inorganic carbon are important to consider as dryland soil amendments are developed.